Analysis of Profitability Ratios at PT Bank Mandiri (Persero) Tbk for The 2020–2025 Period Using A Quantitative Descriptive Approach - Muhammad Rafli; Muhammad Yusuf; Osly Usman; Agus Sulistyono; Rika Vebina Tarigan (Publikasi Indonesia, 2026)
This study aimed to analyze the profitability ratio performance of PT Bank Mandiri (Persero) Tbk during the 2020–2025 period using a quantitative descriptive approach. The data used were secondary data obtained from the company’s annual financial statements and analyzed using key profitability ratios, including return on assets (ROA), return on equity (ROE), net profit margin (NPM), and operating expenses to operating income (BOPO). The analytical method involved presenting the data in tabular form and conducting trend analysis to describe the dynamics of the company’s financial performance. The results indicated that ROA and ROE experienced significant growth until 2023, followed by a decline in the 2024–2025 period. NPM showed highly volatile fluctuations, with a sharp increase up to 2023 and a substantial decline thereafter. Meanwhile, BOPO showed a downward trend, indicating improved operational efficiency, although a slight increase occurred at the end of the period. The study concluded that Bank Mandiri’s profitability performance was dynamic and influenced by both internal and external factors. This research contributed to the understanding of banking financial performance analysis based on profitability ratios in a longitudinal context.